A Legal Analysis on Resolving Recently Growing Online Business Frauds in Bangladesh - Md Adnan Kabir (LAW REFORM, 2022)
In the recent time, the E-commerce sector has been facing serious challenges due to the fraudulent behaviors of a number of E-commerce businesses. Thousands of consumers have lost their money due to these fake transactions. The main purpose of this article is to help to mitigate online business frauds by reviewing the current legislation and regulations in Bangladesh. This research is a descriptive type of research and secondary data and information have been used for study purpose. The study has analyzed existing business laws and provisions, their applicability and deficiencies in reducing online business frauds and dangers. This study finds that there is no committed code or law establishing consumer rights in online businesses. The current laws have not been changed in such a way that online business matters can be handled properly. The study concludes that the legislature may amend existing laws and provisions and also they may consider some foreign countries provisions for taking actions against the fraudulent e-commerce as well as online business organizations. The outcomes of the present study obviously indicate that the risks of online business frauds directly affect consumer behavior when shopping online. Therefore, reducing these risks through undertaking just and proper laws and provisions can increase the trust of the online shopping consumers.